Imaging features of double aortic arch shown by multidetector computed tomography angiography - Jeeyani Hetal; Prajapati Vaishali; Patel Nehal; Shah Shaunak (Wolters Kluwer Medknow Publications, 2010)
We present a three-dimensional reconstructed image of vascular ring in a 2.5-month-old patient, which was obtained using multidetector computed tomography (MDCT). MDCT angiography made an accurate diagnosis of this life-threatening, but correctable, anomaly in an infant with a stridor, repeated respiratory infections and episodes of apnea.